PERBANDINGAN HUKUM TENTANG HUKUMAN MATI MENURUT KITAB UNDANG-UNDANG HUKUM PIDANA NOMOR 1 TAHUN 2023 DAN PENAL CODE OF SINGAPORE: Comparison Of Laws On The Death Penalty According To The Criminal Code Number 1 Of 2023 And The Penal Code Of Singapore - Utari Nabila Andjani; Dian Adriawan D Tawang (Faculty of Law, Universitas Trisakti, 2025)
Indonesia and Singapore are among 68 countries that use the death penalty. The death penalty enforced in Indonesia is stated in the Criminal Code Number 1 of 2023. Singapore is the smallest country but has the highest existence of the death penalty for its people who violate the rules of the Criminal Code. The purpose of this study is to provide a comparative description of criminal acts that are sentenced to death according to Indonesian and Singaporean law and to determine the similarities and differences in the death penalty in Indonesia and Singapore. This type of research is normative law, namely research carried out by reviewing library documents or secondary data. Secondary data collection is a technique for collecting data for this research through literature studies. The results of the data analysis obtained by the State of Indonesia regulate criminal acts that are sentenced to death for crimes: sabotage and crimes during war, premeditated murder, theft, drug abuse, corruption, serious human rights violations. The State of Singapore regulates criminal acts that are sentenced to death for crimes: murder. Similarities in the death penalty, both countries still apply the death penalty and regulate sanctions. The difference regarding the legal system is that Indonesia adheres to the Civil Law legal system and Singapore adheres to the Common Law legal system